Family resilience mediates exposure to adverse childhood experiences on insufficient sleep among children: findings from a population-based study - Baiden, Philip; Vazquez, Christian E.; LaBrenz, Catherine A.; Brown, Fawn A. (Frontiers in Pediatrics, 2024)
Background. Sleep plays a vital role in the well-being of children and adolescents. Researchers have identified adverse childhood experiences (ACEs) as an important factor associated with poor sleep among adolescents. The objective of this study was to examine the mediating role of family resilience on the association between ACEs and insufficient sleep among adolescents in the United States. Methods. Data for this study came from the 2018-2019 National Survey of Children’s Health (N=28,097). The outcome variable in this study was insufficient sleep, and the main explanatory variable was exposure to ACEs. The mediating variable was family resilience. Data were analyzed using binary logistic regression. Results. Based on parent reports, one in five (22.4%) adolescents did not meet the recommended sleep hours on an average night. About half of the adolescents had no ACEs, 24.2% had one ACE, and 14.6% had three or more ACEs. Controlling for the effect of other factors and family resilience, the odds of having insufficient sleep were 1.63 times higher for children exposed to three or more ACEs (AOR=1.63, 95% CI=1.30-2.05). Family resilience partially mediates the association between exposure to ACEs and insufficient sleep. Each additional increase in family resilience decreased the odds of having insufficient sleep by a factor of 12% (AOR=0.88, 95% CI=0.86-0.91). Conclusions. Family resilience partially mediated exposure to ACEs on insufficient sleep. There are modifiable factors that may improve sleep outcomes among adolescents who have been exposed to adversity. Future research can help elucidate findings and establish the directionality of this association.